2015
DOI: 10.1155/2015/610417
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Hyalinizing Granuloma Mimicking Metastatic Lung Cancer

Abstract: Pulmonary hyalinizing granuloma is a very rare benign condition, which usually manifests as solitary and sometimes as multiple pulmonary nodules. Deposition of immune complexes in the lung parenchyma due to hypersensitivity reactions is implicated in the etiology of pulmonary hyalinizing granuloma. A 59-year-old female patient who presented to our clinic with complaints of chest pain and cough had bilateral, multiple, and rounded lesions with regular margins suggesting metastatic lung disease. A transthoracic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…Despite its benign nature, it can often present similarly to metastatic disease3 5 and thus patients can undergo extensive investigation to seek a definitive diagnosis. There is often diagnostic uncertainty around PHG, and the existing literature have indicated that a definitive diagnosis is usually gained only after surgical intervention as in our patient 4 7 8.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite its benign nature, it can often present similarly to metastatic disease3 5 and thus patients can undergo extensive investigation to seek a definitive diagnosis. There is often diagnostic uncertainty around PHG, and the existing literature have indicated that a definitive diagnosis is usually gained only after surgical intervention as in our patient 4 7 8.…”
Section: Discussionmentioning
confidence: 99%
“…Despite its benign nature, it can often present similarly to metastatic disease3 5 and thus patients undergo extensive investigation to seek a definitive diagnosis. As the investigations working up this disease are not without their risks and complications, it is important for clinicians to reflect on an increasingly recognised cause of lung nodules which can lead patients into having a long and invasive course of treatment and rehabilitation.…”
Section: Introductionmentioning
confidence: 99%
“…[ 3 ] Patients usually present with symptoms of cough, dyspnea, and chest pain. [ 4 ] About 25% of patients are asymptomatic. [ 5 , 6 ] If the esophagus is compressed by a tumor, dysphagia can develop.…”
Section: Discussionmentioning
confidence: 99%
“…Final conclusive diagnosis is based on histopathological analysis of the nodule biopsy specimen [8]. PHG is a benign, sometimes recurrent condition, with no predilection for gender that is predominantly multinodular, as in the case reported.…”
Section: Introductionmentioning
confidence: 91%